Effects of simulated training on immune function in elite male handball players - Wei, H.; Wei, H.; Xiao, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The physiological responses induced by various hypoxic training methods have been studied since the training concept of "Living Low-Training High" was introduced by Levine and Stray-Huandersen. However, the immune function of elite athletes under simulated hypoxic training conditions needs further investigation. The purpose of this paper was to study the changes in immune function after 3 weeks of simulated Living Low-Training High (Lo-Hi). This situation consists of sleeping and living in normoxia but training in moderate hypoxia. Comparisons were made between elite male handball players and similarly trained controls. Methods The control subjects (Lo-Lo group, n=7) trained at sea level consistent with the training regime of the experimental group, however they were not exposed to high altitude conditions. Demographic and functional characteristics for this group was as follows: age 19.14±0.69 yr, height 192.1±4.19 cm, weight 86.2±9.32 Kg, body fat 9.27±2.23 %, Power-max 883.3±84.81 Watts). For the experimental group (Lo-Hi group,N=6) the corresponding measures were:, age 19.41±0.61 yrs, height 195.9±6.19 cm, weight 87.6±8.53 Kg, body fat 9.25±1.92 %, Power-max 8973.3±85.18 Watts) Subjects lived and had general training at near sea level. The general training program consisted of technical & tactical training and basic fitness training (2 sessions/day, 150 min/session). The Lo-Hi group received additional aerobic ergometer training at a simulated altitude of 2500m (HR=150- 160bpm, 60min/session, 4 sessions/wk on every other day in one week). All players had a rest each Sunday during the period of observation. Blood leukocytes (Leu) and its constituents: granulocytes (Gran), monocytes (Mono), lymphocytes (Lymph), secretory immunoglobulin A (sIgA), Interleukin-2 (IL-2), soluble Interleukin-2 Recetpor (sIL-2R) and immune suppressive factor (ISF) were measured before training and at the 9th, 16th and 21st day during training. Results The results indicated that Leu, Gran, Mono, Mono%, Lymph, Lymph%, and serum content of sIgA, IL- 2 and sIl-2R did not change significantly (P>0.05) in the Lo-Lo group; Leu, Gran, Mono, Mono%, Lymph, serum content of sIgA, IL-2 and sIl-2R did not change significantly in the Lo-Hi group (P>0.05) compared with the Lo-Lo group; Gran% and Mono were higher (P<0.05) and lymph% was markedly lower (P<0.05) on the 21st day in the Lo-Hi group compared with the Lo-Lo group; Serum content of ISF peaked on the 16th day and was notably higher than the levels pre-training (P<0.01~0.001) and on the 9th day (P<0.05), and ISF was lower on the 21st day than levels on both the 9th day (P<005~0.01) and 16th day (P<0.01~0.001). Conclusions 1. Living and training in a normoxic atmosphere did not significantly affect blood Leu, Gran, Gran%, and serum content of sIgA, serum IL-2 and sIL-2R. 2. Living and training in normoxia and simulated hypoxia did not significantly change the serum content of sIgA, serum IL-2 and sIL-2R. 3. Aerobic training in the simulated hypoxic condition only did not alter Leu, Gran, Mono, Mono%, Lymph, serum content of sIgA, Il-2 and sIL-2R. 4. Serum content of ISF decreased significantly on the 16th day and then increased on the 21st day.